2021
DOI: 10.1055/s-0040-1721337
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Patient with Lemierre Syndrome of the External Jugular Vein: Case Report and Literature Review

Abstract: Introduction Lemierre syndrome (LS) involving the external jugular vein (EJV) is rare, and only a few cases have been reported in the literature. Objectives To report a case of LS involving the external jugular vein as well as to make a review of the literature regarding both diagnosis and management strategies. Data Synthesis We describe a case of LS involving the EJV and review the literature of previously published articles to search for additional cases. A PubMed, Embase, Scopus, and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Due to the rarity of this syndrome in the pediatric population, there are very few reports of atypical presentations. The most common thrombosis locations are the external jugular vein and sigmoid, cavernous, and transverse sinuses (19,20). To this date, no reports of LS presenting with isolated thrombophlebitis of the facial vein have been described in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the rarity of this syndrome in the pediatric population, there are very few reports of atypical presentations. The most common thrombosis locations are the external jugular vein and sigmoid, cavernous, and transverse sinuses (19,20). To this date, no reports of LS presenting with isolated thrombophlebitis of the facial vein have been described in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a study conducted by Schwartz et al focusing on infections involving the EJV identi ed 21 relevant studies (n = 16 cases). 4 In contrast, our literature review diverges from their speci c focus and encompasses patients with isolated EJV thrombophlebitis attributed to various etiologies. After reviewing the abstracts and references, a total of 33 articles comprising solely case reports or case series were identi ed (Table 3).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Some studies have suggested that anatomical variations in the jugular venous system might contribute to this observation. 4,36,37 During our investigation into the underlying cause of thrombosis in our patient, the care team deliberated on the potential presence of Lemierre's syndrome. However, the absence of typical symptoms and sequelae, such as pulmonary septic emboli, the identi cation of GAS as the cultured organism, and the isolated involvement of the EJV, made the diagnosis less likely at that time.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation